Case Study: Asuhan Keperawatan Gerontik Nyeri Pada Pasien Ny. S Dengan Hipertensi di Ruang Sankai Rs Nishihara Keiaien Okinawa Jepang - Rifai, Irfan; Kurniawan, Wasis Eko; Septiani, Febi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Hypertension is a medical condition characterized by an increase in blood pressure above normal limits. It is characterized by a systolic blood pressure of 140 mmHg or higher, or a diastolic blood pressure of 90 mmHg or higher. One of the nursing problems in hypertensive patients that requires special treatment is pain. This research aims to provide pain nursing care to Mrs. S with Hypertension in the Sankai Room of Nishihara Keiaien Hospital, Okinawa, Japan. This research uses a descriptive method with a case study approach. The case study instrument uses a format for documenting nursing care, observation, interviews and physical examination. The results of the research after the nursing care process was carried out for 3 days showed that complaints of pain decreased, complaints of grimaces decreased. It is hoped that by applying deep breathing techniques, treatment actions can be in accordance with established procedures.